Essays on growth, competition and international trade - Rios, Heron Marcos Teixeira (2020)
This thesis is composed of three independent papers. Below follows a brief description of each article. The first paper revisits the competition-innovation debate in light of the recent empirical evidence on the effects of increased exposure to China product competition. From the empirical perspective the evidence is mixed. Faced with fiercer competition, firms in European countries innovate more whereas for the US the effects are negative. In theory, two competing forces are in place. On one hand, more intense competition decreases the profit stream by decreasing markups, the standard Schumpeterian effect. On the other hand, competition may increase the firm’s incentives to gain a technological lead over its competitor increasing the firm’s ability to charge higher markups, the escape competition effect. The extent to which one of the forces dominates will depend on the technological distance between competitors. I argue that changes in the distinct initial level of exposure to foreign competition between Europe and the U.S. can account for part of the responses empirically observed. I build a model of step-by-step innovation carried by incumbents that are subject to an entry shock that replaces the follower with a new, one step ahead competitor. I calibrate the model to the U.S. and Europe, pre and post China’s WTO accession. The results suggest a stronger negative effect on innovation for the U.S. relative to Europe. In the second paper, I investigate how static distortions present in the sectoral goods market affect growth incentives in open economies. In the model, capital accumulation and exogenous technology adoption jointly generate output growth. Static distortions distance the economy from the actual productivity profile across sectors changing the country specific real rate of return on capital accumulation in the world balanced growth path. I calibrate the model for the Mexican economy between 1995-2011, a period of stagnation of per capita income. Using the World Input-Output Database I retrieve distortions directly from data through statistics implied by the model. Counterfactual exercises show that aggregate losses could be as high as 54%. Lastly, the third paper is co-authored with Pedro Cavalcanti Ferreira and Alberto Trejos. The commercial war stirred by the Trump administration is only one among many episodes of protectionism policies imposed by countries in different historical moments. They include in most cases aggressive increase in import tariff, among other forms of barriers to trade, target at different types of goods. In this article, we develop an extension of the dynamic trade model, combining a static two-goods and two-factors Heckscher-Ohlin model with a two-sector growth model. In the model the two intermediate goods, produced with capital and labor, are tradable and used in the production of investment and consumption goods, which are not tradable. Our main goal is to analyze how increases in import tariff on a particular type of good affects the production choices and trade pattern of the economy. We characterize the dynamic properties of the model and show that there is only one stable steady state. Simulation results show that the economy will produce less of both consumption and investment goods under autarky for low and high levels of capital stock per worker. We also find that total GDP may be lower under free trade in comparison to autarky due to price effects.